ANALYSIS OF SPARE PARTS REQUIREMENTS BASED ON THE FAILURE RATE OF A COMPONENT USING THE POISSON PROCESS METHOD IN A CASE STUDY AT PT. XYZ - Tamitakarza, Herdi; Ferryanto, Ferryanto; Suweca, I Wayan (Jurnal Rekayasa Mesin, 2025)
This study presents the conclusions drawn from previous data analysis, highlighting several significant key findings. Firstly, an evaluation using a risk matrix revealed that the critical subsystem for the CC 206 Locomotive is the Diesel subsystem, which consists of four important spare part components: The respective MTTF values for the Injector Nozzle, Inverter, Seal Output, and Retainer are 29.292 hours, 18.943,1 hours, 13.442,1 hours, and 26.318,1 hours. Furthermore, the annual requirements for these components were calculated using a Poisson process based on their respective MTTF values. These findings provide valuable insights into the importance of these components and their annual requirements, which in turn will significantly contribute to the efficient maintenance and operation of the CC 206 locomotive. It is estimated that the annual requirements for these components are 21 units for the injector nozzle, 31 units for the inverter, 42 units for the seal output, and 23 units for the retainer. This study proposes a novel application of the Poisson process to estimate the annual requirement of spare parts based on actual component failure rates and their corresponding MTTF. The method offers the advantage of being data-driven, probabilistic, and suitable for systems with constant failure rates, making it highly effective for optimizing inventory levels in railway maintenance. This research provides a new insight into quantitative spare part planning that improves reliability-based inventory strategies in Indonesian railway operations.